Downregulation of microRNA-218 is cardioprotective against cardiac fibrosis and cardiac function impairment in myocardial infarction by binding to MITF - Qian, Linfeng (Aging (Albany NY), 2019)
Objective: This study is intended to figure out the function of microRNA-218 (miR-218) together with microphthalmia-associated transcription factor (MITF) on the cardiac fibrosis and cardiac function impairment in rat models of myocardial infarction (MI). Results: The rats with MI exhibited cardiac function impairment, cardiac fibrosis, oxidative stress, cardiomyocyte apoptosis, as well as inflammatory injury. Additionally, upregulated miR-218 and downregulated MITF were detected in cardiac tissues of MI rats. MI rats injected with miR-218 inhibitors or overexpressed MITF exhibited elevated MITF expression, improved cardiac function, and diminished pathological damages, infarct size, cardiomyocyte apoptosis, cardiac fibrosis, oxidative stress as well as inflammatory injury in cardiac tissues. Furthermore, downregulated miR-218 and MITF aggravated the conditions than downregulation of miR-218 alone in MI rats. Methods: MI models were performed in rats, and then the rats were injected with miR-218 inhibitors and/or MITF overexpression plasmid to elucidate the role of miR-218 and/or MITF on the cardiac function, pathological damage, cardiac fibrosis, angiogenesis, oxidative stress and inflammatory injury of cardiac tissues in MI rats by performing a series of assays. Conclusion: Collectively, we found that the suppression of miR-218 alleviates cardiac fibrosis and cardiac function impairment, and stimulates angiogenesis in MI rats through inhibiting MITF.